The Madrasa Principal Leadership: Its Role in Fostering Qur'an Reading Culture - Ayu, Zaituna Mas; Zulyana, Rahmi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Fostering a culture of reading the Qur'an can be a supporting factor in achieving the vision and mission of the madrasa. The development of a culture of reading the Qur'an can also be an effort made by madrasas to help students who have not been able to read the Qur'an properly and correctly. The madrasa principal plays an important role in fostering a culture of reading the Qur'an in the madrasa. This study aims to determine the role of the madrasa principal in fostering a culture of reading the Qur'an at Madrasa Aliyah Negeri 2 Bandar Lampung. data obtained through the process of interviews, observation, and documentation. Sources of research data were obtained from informants who were trusted and considered capable of answering the problems studied, namely the head of the madrasa, teachers, and students at Madrasa Aliyah Negeri 2 Bandar Lampung, Indonesia. The research data were analyzed in several stages, namely data reduction, data presentation, data verification, and conclusion. The validity of the research data was tested by triangulating methods and triangulating sources. According to the study's findings, the madrasa program plays the role of the madrasa principal in fostering a culture of Qur'an reading at Madrasa Aliyah Negeri 2 Bandar Lampung to achieve the madrasa's vision and mission. The leadership of the madrasa principal in fostering a culture of reading the Qur'an at Madrasa Aliyah Negeri 2 Bandar Lampung can be seen in his role, which always directs the madrasa program to realize the vision and mission of the madrasa. The madrasa principal does several things to foster the reading of the Qur'an with the abilities he has, namely: The ability of the madrasa head in terms of personality is that, as a leader, he is responsible for all the authority in the madrasa.